Nutrient-based ecological consideration of a temporary river catchment affected by a reservoir operation to facilitate efficient management - Tzoraki, Ourania A.; Dörflinger, Gerald; Kathijotes, Nicholas; Kontou, Artemis (My University, 2014)
The water quality status of the Kouris river in Cyprus was examined in order to fulfil the requirements for ecological quality as defined by the Water Framework Directive-2000/60/EC. Nitrate concentration (mean value) was increased in the Limnatis (2.8 mg L−1) tributary in comparison with the Kryos (2.1 mg L−1) and Kouris (1.0 mg L−1) tributaries depicting the influence of anthropogenic activities. The total maximum daily nutrients loads (TMDLs) based on the flow duration curves approach, showed that nutrients loads exceeded threshold values (33.3–75.6% in all hydrologic condition classes in the Kouris tributary, and 65–78% in the Limnatis tributary) especially under low flow conditions. The TMDL graph is intended to guide the temporal schedule for chemical sampling in all hydrologic classes. Kouris reservoir is an oligotrophic system, strongly influenced by the river’s flash-flood character but also by the implemented management practices. Kouris river outflow, which was reduced to one-tenth in the post dam period altered the wetland hydrologic network and contributed to the decrease of aquifer thickness. Continuous evaluation and update of the River Basin Management Plans will be the basis for the sustainable development of the Kouris basin.
Keywords: Kouris river; Cyprus; Ecological quality; Nitrate concentration; Kouris river; Cyprus; Ecological quality; Nitrate concentration